The energy politicization of the Russian Federation and the dialectic of the capitalist system - De Lucena, Arthur Máximo (2025)
The article aims to analyze the concept of natural resources and their political use by the Russian Federation. For this, energy trade, Russia's political bargaining process, and the capitalist system will be considered through the dialectical and historical materialism method through the following guiding question: How does the Russian Federation use its energy resource as a political platform?